Spare - Harry, Prince (New York Random House Audio, 2023)
At twenty-one, he joined the British Army. The discipline gave him structure, and two combat tours made him a hero at home. But he soon felt more lost than ever, suffering from post-traumatic stress and prone to crippling panic attacks. Above all, he couldn?t find true love.
Keywords: British Kingdom